2022
DOI: 10.3389/fmicb.2022.863142
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Loop-Mediated Isothermal Amplification Assay for Rapid Detection of Yersinia pestis

Abstract: Rapid detection of Yersinia pestis, the causative agent of plague, is essential during field investigations to enable prompt control measures for prevention of the spread of the disease. Affordable, efficient, reliable, and simple detection assays are extremely useful, particularly in plague-endemic regions with limited resources. We developed a loop-mediated isothermal amplification (LAMP) assay that detects Y. pestis within 30 min by simply incubating at 65°C on a dry bath heater. The assay targeted the caf1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The inhibiting substances may be present in the analyzed samples and may affect the sensitivity of an assay (Kaneko et al, 2007 ; Nkouawa et al, 2010 ). Previous studies have reported the presence of inhibiting substances from DNAs of mouse liver, spleen, and lung in PCR (Feng et al, 2018 ; Bai et al, 2022 ). Our results also may suggest the presence of inhibiting substances from spleen-derived DNAs that have occurred in the testing.…”
Section: Discussionmentioning
confidence: 98%
“…The inhibiting substances may be present in the analyzed samples and may affect the sensitivity of an assay (Kaneko et al, 2007 ; Nkouawa et al, 2010 ). Previous studies have reported the presence of inhibiting substances from DNAs of mouse liver, spleen, and lung in PCR (Feng et al, 2018 ; Bai et al, 2022 ). Our results also may suggest the presence of inhibiting substances from spleen-derived DNAs that have occurred in the testing.…”
Section: Discussionmentioning
confidence: 98%